Hypersensitivity pneumonitis: A new strategy for serodiagnosis and environmental surveys. (April 2019) - Bellanger, Anne-Pauline; Reboux, Gabriel; Rouzet, Adeline; Barrera, Coralie; Rocchi, Steffi; Scherer, Emeline; Millon, Laurence
Abstract: We propose a strategy for serodiagnosis of hypersensitivity pneumonitis (HP): 1) question patients about their private or occupational activity, or visit him on site; 2) select panels of six somatic specific antigens appropriate for each type of exposure; 3) and use ELISA to test concomitantly two recombinant antigens highly specific to Farmer's lung, Metalworking-fluid HP, and for Bird fancier's lung. The serodiagnosis provides an immunological argument that may complete radiological, functional lung exploration and clinical features; 4) If the serodiagnosis is negative but the suspicion of HP is strong, a microbial analysis of the patient's specific exposure is conducted; 5) "A la carte" antigens are produced from the microorganisms isolated in the patient's environment sample and tested; 6) Finally, the patient may be asked to undergo a specific inhalation challenge with the offending antigens in a safety cabin, or to avoid his usual environment for a few days. Graphical abstract: Image 1 Highlights: A six-step strategy for serodiagnosis of hypersensitivity pneumonitis is recommended. Three kinds of antigens must be used: somatic, recombinant and "a la carte" antigens. Microbiological surveys are helpful to select antigens or make "a la carte" antigens. As proof, re-exposure to the natural environment or commercial extract is necessary.